Reflexão Bibliotecária no ato de mediar: entre a racionalidade e a concepção representacionista da informação - CASTRO, Jetur Lima de (Universidade Federal do Pará, 2019)
It discusses library mediation from Fred Dretske informational action, the findability and usability of information through affordances in Jerome Gibson, and communicative action on the basis of Habermasian thinking from a critical and interpretive approach. In methodological terms, this is a theoretical research, with a critical and interpretive approach, which tries to develop the informational perception of the librarian in informational environments, which is responsible for the formation of information patterns that direct the perception-action of its users. In conclusion, it is considered that information as a phenomenon of cognitive action emerges by fissuring the technical structures of information theory by developing in the discursive act and in the intersubjective dialogue of the librarian as mediator and in the subjects that seek the knowledge available in libraries.